Scale Economies and Industry Agglomeration Externalities: A Dynamic Cost Function Approach - Paul, Catherine J. Morrison; Siegel, Donald S (American Economic Review, 1999)
Scale economies and agglomeration externalities are alleged to be important determinants of economic growth. To assess these effects, we outline and estimate a microfoundations model based on a dynamic cost function specification. This model provides for the separate identification of the impacts of externalities and cyclical utilization on short- and long-run scale economies and input substitution patterns. We find that scale economies are prevalent in U.S. manufacturing, cost savings and scale effects often attributed to internal inputs may be due to external factors, and supply-side agglomeration effects are greater than demand-side, especially in the long run. (JEL O47, E23)